2015
DOI: 10.1007/s11242-015-0587-5
|View full text |Cite
|
Sign up to set email alerts
|

Two-Scale Preconditioning for Two-Phase Nonlinear Flows in Porous Media

Abstract: Solving realistic problems related to flow in porous media to desired accuracy may be prohibitively expensive with available computing resources. Multiscale effects and nonlinearities in the governing equations are among the most important contributors to this situation. Hence, developing methods that handle these features better is essential in order to be able to solve the problems more efficiently. Focus has until recently largely been on preconditioners for linearized problems. This article proposes a two-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Comprehensive studies of nonlinear DD schemes in the field of fluid dynamics can be found in [36,37,38]. For articles strictly related to porous media flow models, we refer to [39,40] for an overview of different overlapping domain decomposition strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Comprehensive studies of nonlinear DD schemes in the field of fluid dynamics can be found in [36,37,38]. For articles strictly related to porous media flow models, we refer to [39,40] for an overview of different overlapping domain decomposition strategies.…”
Section: Introductionmentioning
confidence: 99%
“…Employing the polynomial chaos framework admits low-cost post-processing of the output to obtain statistics of interest. Skogestad et al (2015) propose a two-scale nonlinear preconditioning technique for multiphase flow problems in porous media that allows for incorporating physical intuition directly in the preconditioner. The developed preconditioner exhibits good scalability properties for challenging problems regardless of dominant physics.…”
Section: Research Area B: Numerical Methodsmentioning
confidence: 99%
“…Due to different hydrogeological properties of the different rocks, domain decomposition (DD) methods appear to be a natural way to solve efficiently two-phase flow models, see [92,93,2], and also [57,85,86,83,82]. This paper complements [3], where a global-in-time domain decomposition method for this nonlinear and degenerate parabolic problem was proposed (without analysis), using the Optimized Schwarz Waveform Relaxation algorithm (OSWR) with Robin or Ventcell transmission conditions.…”
Section: Introductionmentioning
confidence: 99%